Seeds of terror an eyewitness account of Al-Qaeda's newest center of operations in Southeast Asia - Ressa, Maria (Free Press, a division of Simon & Schuster, Inc., 2003)
An eyewitness account of Al-Qaeda's newest center of operation in Southeat Asia.